Pengaruh Peran Kepala Sekolah, Kepuasan Kerja, dan Iklim Organisasi terhadap Motivasi Kerja Guru Sekolah Dasar Negeri: The Influence of the Principal's Role, Job Satisfaction, and Organizational Climate on the Work Motivation of Public Elementary School Teachers - Sari, Elok Faiqoh Ragil Mekar; Rasiman, Rasiman; Wuryandini, Endang (ITScience (Information Technology and Science), 2024)
Teacher work motivation is an essential factor in the success of the teaching and learning process. However, in Kedu District, Temanggung Regency, low teacher motivation was found due to a lack of support from the principal, ineffective policies, and an unconducive work environment. Teachers who do not feel supported or appreciated perform less than optimal. This study aims to examine the influence of the role of the principal, job satisfaction, and organizational climate on teacher work motivation. This study involved all public elementary school teachers in Kedu District as the population, totalling 196 people, with a selected sample of 132 respondents. Data collection was carried out through questionnaires and documentation. This study has undergone a validity test with Pearson correlation and a data reliability test with Cronbach alpha. Data were analyzed using descriptive methods, assumption tests, and hypothesis testing through simple regression analysis and multiple linear regression. The results of the study showed that the role of the principal influences teacher work motivation, job satisfaction influences teacher work motivation, and organizational climate influences teacher work motivation. Simultaneously, the role of the principal, job satisfaction, and organizational climate significantly affect teacher work motivation. This study provides suggestions so that principals can establish good relationships with teachers. In addition, there is a need for teacher career development and welfare programs to be carried out consistently.